173k views
3 votes
What is the answer for this?

What is the answer for this?-example-1
User SDD
by
4.6k points

2 Answers

4 votes

Answer:

is no

Explanation:

User Stephenalexbrowne
by
5.1k points
3 votes

Answer:

  • f(g(x)) = x - 39/4
  • g(f(x)) = x - 39
  • B. No

Explanation:

Given functions:

  • f(x) = 1/4(x + 13)
  • g(x) = 4(x - 13)

Simplified f(g(x)) and g(f(x))

  • f(g(x)) = 1/4(4(x - 13) + 13) = x - 13 + 13/4 = x - 39/4
  • g(f(x)) = 4(1/4(x + 13) - 13) = x + 13 - 4*13 = x - 39

Checking if f(x) and g(x) are inverse functions:

  • f(x) = 1/4(x + 13), substituting f(x) and x, with x and g(x)
  • x = 1/4(g(x) + 13)
  • 4x = g(x) + 13/4
  • g(x) = 4x - 13/4

As we see g(x) is different from the given, so the functions are not inverse

User Melvin Sowah
by
5.6k points